Reindeer husbandry and forestry in the reindeer herding district of Poikajärvi during the years 1963 — 1984 - Kupiainen, Katarina; Nieminen, Mauri (Rangifer, 2010)
Reindeer husbandry and forestry are practised in Finland in the same areas and practisers of these sources of livelihood not been able to avoid conflicts. Large clear-cutting and ploughed areas especially have diminshed the reindeer's winter ranges. In winter the reindeer digs ground lichens (Cladina spp) under the snow and when the snow surface becomes harder it begins to pasture upon arboreal lichens (Alectoria and Bryoria spp.). Fields of lichen are, however, very worn and the best forests with arboreal lichens have been cut. The area of the reindeer herding district of Poikajarvi (66°30' — 67°10'N) is 2507 km2 of which state owned land is 1474 km2 (59%). The average reindeer density (counted reindeer) of the years 1963 — 1984 has been 1.5 reindeer/km2. During the last 20 years 9.8% of the state owned land of Poikajarvi has been treated with regeneration cutting, mostly with clear-cuttings, and 10.6% with thinning cuttings. With different soil preparation methods 8.7% has been treated, most of it by ploughing. About 24% of the damp sites have been clearcut and ploughed. The estimated cutting quantity of state owned forests has continually increased since 1976 and in 1984 it was about 140 600 m3. Since 1963 the number of counted reindeer of the reindeer herding district has decreased by 60 reindeer yearly. It has varied between 4939 and 2866 reindeer. In the years 1963 — 1984 on average 1425 reindeer were slaughtered yearly. The calves' share of the slaughtered reindeer has increased and in the last few years it has been almost 80%. The average reindeer meat production has been 36 400 kg a year. In Poikajarvi supplemental feeding of reindeer has been practised since 1969. The amount of hay used for it has increased from about 5.5 kg to nearly 20 kg per counted reindeer. At the same time the number of counted and slaughtered reindeer and. meat production has decreased. Rennäringen och skogsbruket i Poikajärvis Renbeteslag under åren 1963 — 1984. Abstract in Swedish / Sammandrag: Renskötsel och skogsbruk utövas i Finland ungefär på samma områden och man har inte kunnat undvika konflikter mellan dessa näringsgrenar. Omfattande kalhyggen och plöjningar har minskat, speciellt renarnas vinterbiotoper. Under vintern gräver renen efter lavar (mest Cladina spp.) under snötäcket och när skare bildas börjar den beta hänglavar (Alectoria och Bryoria spp.). Lavmarkerna är mycket slitna och de bästa hänglavsskogarna är avverkade. Poikajärvi renbeteslags (66°30' — 67°10'N) areal är 2507 km2, varav 1474,5 km2 (59%) är statsägd mark. Under åren 1963 — 1984 har den genomsnittliga rentätheten innräknade renar varit 1,5 ren/km2. Under de senaste 20 åren har 9,8% av den statsägda marken inom renbeteslaget slutavverkats, huvudsakligen kalhuggits, och 19,6% av densamma har behandlats med beståndsvårdande huggningar. Markberedning, huvudsakligen genom plöjning, har utforts på 8,7% av arealen. Av de friska moarna har ungefär 24% blivit kalhuggna och plöjda. Avverkningskvantiteten inom de statsägda skogarna har hela tiden ökat och 1984 va den ungefär 140 600 km3. Sedan 1963 har totalantalet inräknade renar sjunkit med i genomsnitt 60 renar per år. Det har varierat mellan 4939 och 2666 djur. Under åren 1963 — 84 slaktades i genomsnitt 1425 renar pr år. Kalvandelen därav har ökat och de senaste åren har den varit nästan 80%. Den genomsnittliga köttproduktionen har varit 36 400 kg per år. Stödutfodring av renar har tillämpats i Poikajärvi sedan 1969. Den använda hömängden har vuxit från ungefär 5,5 kg till nästan 20 kg per inräknad ren och år. Samtidigt har såvål renantal, slaktdjursantal och köttproduktion siunkit. Porotalous ja metsätalous Poikajärven paliskunnassa vuosina 1963 — 1984. Abstract in Finnish / Yhteenveto: Poro- ja metsätaloutta harjoitctaan Suomcssa paljolti samoilla alucilla eikä ristiriitoja näiden elinkeinojen harjoittajien välillä ole voitu välttää. Laajat metsien avohakkuut ja aurakset ovat supistaneet erityisesti porojen talvilaitumia. Talvclla poro kaivaa jäkälää (Cladina sp..) lumen alta ja siirtyy hangen kovetessa syömään luppoa (Alectoria ja Bryoria spp.). Jäkäliköt ovat kuitenkin kovin kuluneita ja parhaat luppometsät on hakattu. Poikajärven paliskunnan (66°30' — 67°10'N) pinta-ala on 2507 km2, josta valtionmaata 1 474.5 km2 (59%). Vuosien 1963 — 1984 keskimääräinen lukuporotiheys on ollut 1.5 poroa/km2. Viimeisen20 vuoden aikana on Poikajärven valtionmaan alasta käsitelty uudistushakkuilla, pääasiassa avohakkuilla, 9.8% ja kasvatushakkuilla 19.6%. Erilaisilla maanmuokkausmenetelmillä on käsitelty 8.7%, valtaosa auraamalla. Tuoreista kankaista on avohakattu ja aurattu noin 24%. Paliskunnan valtionmetsien arvioitu hakkuukertymä on vuodesta 1976, lähtien jatkuvasti kasvanut ja oli vuonna 1984 noin 140 600 m3. Vuodesta 1963 lähtien lukuporojen määrä on vähentynyt keskimäärin 60 porolla vuodessa. Määrä on vaihdellut 4939 ja 2866 poron välillä. Vuosina 1963 — 1984 on teurastettu keskimäärin 1 425 poroa vuodessa. Vasojen osuus teurastetuista on kasvanut ja viime vuosina se on ollut lähes 80%. Poronlihantuotanto on ollut keskimäärin 36 400 kg vuodessa. Porojen lis'äruokintaa on Poikajärven paliskunnassa harjoitettu vuodesta 1969 lähtien. Lisäruokintaan käytetyn heinän määrä on kasvanut noin 5.5 kg:sta lähes 20 kg:an lukuporoa kohti. Samanaikaisesti on lukuporojen ja teurastettujen määrä sekä lihantuotanto laskenut.